Selected Elements of the Potential of the Competitiveness of Travel Agencies in the Tourism Market of the Retired in Poland - Kociszewski, Piotr (Studia Oeconomica Posnaniensia, 2017)
The aim of this study is to identify and characterize selected elements of the potential competitiveness of travel agencies in the tourism market of the retired in Poland. The paper consists of two main parts - theoretical and a presentation of the results of the empirical research. According to the author in the case of tourism dedicated to the retired a key building block for competitive advantage is the quality - understood in a broad sense. A summary of the results of the research conducted among the providers of tourism for the retired can be an important source of information for both existing and potential bidders.